(untitled) (Research, Society and Development, 2021)
This work aims to develop a cluster of information about the oral manifestations of candidiasis, their diagnosis and treatments, which can serve as a base for consultation for dentistry students and professionals in the field. A descriptive narrative literature review was carried out, using scientific articles available in online databases such as PubMed, BVSalud, SciELO, Lilacs and Google Scholars as a bibliographic base, these are presented in Portuguese and English. Oral Candidiasis is a fungal infection generally considered common, caused by the growth of species of the fungus Candida sp in the oral cavity, highlighting the opportunistic nature of the infection and the reduced defense of the host in which it develops. Importantly, oral candidiasis is not a single infectious entity, it has four distinct forms based on clinical presentations, which are: pseudomembranous candidosis, acute erythematous candidiasis, chronic erythematous candidiasis and chronic hyperplastic candidiasis, although, recently, pseudomembranous candidiasis no longer classified and now encompasses only in a form based on the duration of signs and symptoms After analyzing and absorbing the information contained in all the material used as a bibliographic base for the development of this work, it was concluded that it is extremely important that dentists are updated about oral candidiasis, so that they are able to perform a correct diagnosis of these as well as to choose the best therapeutic option, individually and always seeking to avoid the development of microorganisms resistant to the drugs used.